Produtividade do milho safrinha e modificações químicas de um latossolo em sistema plantio direto em função de espécies de cobertura após calagem superficial - Andreotti, Marcelo [UNESP]; Araldi, Marcelo; Guimarães, Vandeir Francisco; Furlani Junior, Enes [UNESP]; Buzetti, Salatiér [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2008)
Modern agriculture is undergoing profound changes, with demands for more efficient management practices in the production systems used in each area. The objectives of this study were: to evaluate the effect of different covering species on a no-tillage system; to find the results of lime application on soil surface after sowing those forage species; measure the effects on soil chemical properties and subsequent effect on corn yield; and to determine the dry matter produced by each species used. The experiment was conducted on November, 2002, in the town of Palotina, Paraná State, Brazil. A randomized block design was used, with 4 repetitions, in a 2x6 factorial scheme -two depths of soil sampling (0-10 and 10-20 cm) and six types of forage covering on the soil (Mucuna deeringiana, Crotalaria juncea, Setaria incana, Pennisetum glaucum and Eleusine gracilis, as well as a mix of all these species). 3 t ha-1 of dolomitic limestone were applied in total surface area, without amending. The covering species associated with the surface limestone application showed improvement in soil fertility, mainly in the layer of 10-20 cm, with prominence to Eleusine gracilis, Crotalaria juncea and Setaria incana. Eleusine gracilis and Crotalaria juncea featured the largest dry matter production; however, the great amount of straw of Eleusine gracilis damaged the productivity of corn. Grain and corn straw productivity was higher when previously cultivated along with Setaria incana and the mix of forage species covering.

A agricultura moderna passa por mudanças profundas, com exigências de manejo mais eficientes para o sistema de produção utilizado em cada região. O trabalho teve por objetivo avaliar o efeito de espécies de cobertura, em SPD, e da calagem em superfície do solo, após semeadura dessas espécies, sobre as propriedades químicas do solo e o efeito subseqüente na produtividade do milho, além de determinar a biomassa seca produzida por estas espécies. O experimento foi instalado em novembro/2002 no município de Palotina, Estado do Paraná. Utilizou-se o delineamento de blocos casualizados, com quatro repetições, num fatorial 2x6 - duas profundidades de amostragem de solo (0-10 e 10-20 cm) e seis espécies de cobertura (mucuna anã, crotalária juncea, capim moa, milheto, pé-de-galinha gigante e um mix destas espécies). Foram aplicadas 3 t ha-1 de calcário dolomítico em superfície, sem incorporação. As espécies de cobertura associadas à calagem em superfície proporcionaram melhoria na fertilidade do solo, principalmente na camada de 10-20 cm, destacando-se o pé-de-galinha gigante, crotalária juncea e capim moa. O pé-de-galinha gigante e a crotalária juncea apresentaram as maiores produtividades de massa seca, entretanto, o pé-de-galinha gigante reduziu a produtividade do milho. A produtividade de grãos foi superior precedida do capim moa e do mix das espécies.
Winter corn yield and chemical modifications in latosol as a function of covering species after lime application under no-tillage system
Keywords: green manure; forage species; nutrient contents; Zea mays; adubos verdes; espécies forrageiras; teor de nutrientes; Zea mays